Development of curriculum in Community Pediatrics for fourth-year medical students at Angeles University Foundation - Lopez, Maria Lita L.
This capstone project on community pediatrics for 4th-year medical students, emphasise the pivotal role of community service in addressing the health needs of children and families within diverse communities. This program focuses on holistic healthcare delivery, encompassing health promotion, preventive care, family support, and advocacy.